Content Analysis of Al-Islam and Kemuhammadiyahan Values on Multivariable Calculus Materials - Soebagyo, Joko; Putri, Dzulhijjah Atdina; Dewi, Nikita (Jurnal Pendidikan MIPA, 2022)
The purpose of this research is to build a category of vector field material in Multivariable Calculus learning into the values of Al Islam and Muhammadiyah. The content analysis method uses MaxQDA to code the terms that emerge from the interview texts generated by the participants related to the intersection of the two subjects. The selection of participants is important in order to avoid bias in the description of the interview. Participants were selected 5 out of 31 students based on their knowledge of Multivariable Calculus material and experience in participating in organizational activities of the Muhammadiyah Student Association and the Orientation of Islamic Fundamentals. The results showed that there were three key categories, namely, death, hard work, and brotherhood. Since the vector principle is the same as the beginning of life and the final destination of a person, vector material is closely related to death. Likewise, integral material has a connection with hard work because the principle of line integral can be seen in line with the efforts made by someone. The vector field material is related to the theme of brotherhood because the principle of the vector field is in groups that can be seen as a collection of people. Keywords: vector field, islam, muhammadiyah, multivariable calculus. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp751-764